Isoniazid- and rifampicin-induced thrombocytopenia - Yakar, Fatih; Yildiz, Namsan; Yakar, Aysun; Kilicaslan, Zeki (My University, 2013)
Treatment of tuberculosis has many side effects. Thrombocytopenia is a serious side effect of such treatment and occurs mostly due to rifampicin (RIF). There are very few reported cases of thrombocytopenia due to isoniazid (INH). An 18-year-old female patient was diagnosed with smear-positive pulmonary tuberculosis. A four-drug regimen [INH, RIF, ethambutol (EMB), and pyrazinamide (PZA)] was given. After the development of thrombocytopenia, the drug treatment was stopped, and a thrombocyte suspension was given until a normal thrombocyte count was obtained. After several start-stop trials, first INH and then RIF were identified as the possible causes of thrombocytopenia and were removed from the regimen. The patient was treated with EMB, streptomycin, PZA, and moxifloxacin with no further development of thrombocytopenia. The current case shows that antituberculosis drugs other than RIF and PZA may be responsible for the development of thrombocytopenia.
Keywords: rifampicin-induced thrombocytopenia